Learning with and beyond the body: The production of mobile architectures in a ballet variations class. Issue 1 (1st January 2022) - Hollett, Ty; Peng, XinYun; Land, Susan
ABSTRACT: Background: This paper examines ensemble learning in the context of ballet. We use more-than-representational theory to account for the "invisible" dimensions of ensemble learning, such as sensations, energy, or intensity that bodies sense, circulate, and evoke in others. We illuminate the mobile architectures that emerge in ensemble learning. Mobile architectures emerge when a performance (i.e., dance, athletic, drama), event (i.e., protest, sermon), or environment (i.e., classroom, makerspace) becomes charged as energy is evoked and circulated among bodies. Methods: We describe eighteen months of video-recorded inquiry of teaching and learning in a weekly classical ballet variations class. We used interaction analysis to understand how sensations and energies move (among) bodies during learning. Findings: Through our analysis, we show: 1) How mobile architectures form and dissolve, particularly as instructional time begins; 2) How audible expressions communicate energy and modulate ensemble learning and 3) How instruction transforms as the ensemble comes together and pulls apart. Contributions: This paper contributes a deeper understanding of how learners attune to the relational complexity of learning. It offers accounts of the more-than-representational dimensions of embodiment and calls for further attention beyond the bodies of embodied learning (physical, gestural, tool-mediated dimensions) and toward the intensities, or energies, that those bodies produce together.